Analisis Rendahnya Partisipasi Politik pada Pemilihan Kepala Desa Tahun 2021 : Studi Kasus di Desa Mburukulu, Kecamatan Pahunga Lodu, Kabupaten Sumba Timur - Afliana L. Atamina; Frans B.R Humau; Boli Tonda Baso (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study examines the low level of community political participation in the 2021 Village Head Election (Pilkades) in Mburukulu Village, Pahunga Lodu District, East Sumba Regency. This phenomenon is interesting to study because the participation rate decreased from 79.5% in 2015 to 59.8% in 2021. This study aims to analyze the factors causing the low level of community political participation and the impact of these factors on Indonesian democracy if left unchecked and the importance of increasing political participation. Mburukulu Village in the 2021 Village Head Election (Pilkades). This study uses a descriptive qualitative method, relying on data from interviews, observations, and field documentation. The analysis is based on Ramlan Surbakti’s Political Participation theoretical framework (regarding socio-economic factors and political awareness). Based on Ramlan Surbakti’s theory, it explains that low participation is caused by political awareness, trust in the political system and other factors. The results of the study indicate that low political participation is characterized by: First, low public trust in the village political system, where people believe that participating does not bring change or has no impact on their lives. Second, low public political awareness. This condition creates apathy and a parochial-passive political culture, eliminating citizens’ initiative to get involved in the election process. Second, third, the socio-economic situation of the community where the orientation is on work and economic needs of the community, or the dominance of daily economic pressures. The Mburukulu community, whose occupations are predominantly farmers, livestock breeders, and fishermen, influences motivation to get involved, namely prioritizing work that provides measurable financial benefits, making political participation a secondary choice with long-term benefits.